The Effect of Discovery Learning on Students' Mathematical Discovery Learning Skill - Suratno, Joko (IJRDO- Journal of Educational Research, 2019)
Mathematical discoveries are useful in supporting science and technology development. Nevertheless, there was not as much attention about discovery of mathematics in the school environment. Therefore, students need learning environment so they could learn to study who to discover mathematics. The research aims to analyze the impact of the combining of technology in discovery learning on students’ skill in discovering mathematics. In addition, the research examines the influences of other factors, namely school qualification and prior knowledge. The research was a quasi-experimental with posttest-only design. Based on analysis of data, it was able to be concluded that the learning factor did not effect on students‘ skill in discovering mathematics and there were effects of qualifications of school and prior knowledge. There was a significant interaction between approaches of learning and school qualifications on the students' skill in discovering mathematics. The interaction between approach of learning and prior knowledge; between the school qualification and prior knowledge; and among approach of learning, qualifications of school, and prior knowledge on the students' skill in discovering mathematics was no significant. Integrating technology in discovery learning be able to be applied in teaching and learning of mathematics especially in high level of qualification of school and high level of prior knowledge of students to improve their skill in discovering mathematics.